Time-varying effect of oil market shocks on the stock market - Kang, Wensheng; Ratti, Ronald A.; Yoon, Kyung Hwan (Journal of Banking & Finance, 2015)
A mixture innovation time-varying parameter VAR model is used to examine the impact of structural oil price shocks on U.S. stock market return. Time variation is evident in both the coefficients and the variance-covariance matrix. The standard deviations of the demand side structural shocks reached forty year peaks during the global financial crisis and have remained high since. In the real stock return equation the coefficient of global real economic activity has declined since the late 1990s and that of oil-market specific demand oil shock has been lower since the early 1990s than before. The structural oil shocks account for 25.7% of the long-run variation in real stock returns overall, with substantial change in levels and sources of contribution over time. The contribution of shocks to global real economic activity to real stock return variation rose sharply to 22% in 2009 (and remains 17% over 2009-2012). The contribution of oil-market specific demand price shocks rose unevenly from 5% in the mid-1970s to about 15% in 2007, with a subsequent decline. The contribution of oil supply shocks has trended downward from 17% to 5% over 1973-2012.